THE INFLUENCE OF ENVIRONMENTAL ACCOUNTING KNOWLEDGE, ENVIRONMENTAL SENSITIVITY, AND CSR KNOWLEDGE ON ACCOUNTING STUDENTS ENVIRONMENTAL SUSTAINABILITY BEHAVIOR - Jannah, Fitriyatul; Wulandari , Anis (Faculty of Economics and Business University of Mataram, 2024)
This research aims to analyze the influence of environmental accounting knowledge (EAK), environmental sensitivity (ES), and corporate social responsibility knowledge (CSR-K) on pro-environmental behavior in accounting students. Purposive sampling was used to select samples that were analyzed using multiple linear regression. The research results show that ES and CSR-K significantly affect pro-environmental behavior, while EAK has no effect. These findings indicate that environmental accounting knowledge has been unable to encourage sustainable behavior, while environmental sensitivity factors and CSR knowledge play an essential role in promoting sustainable behavior. This research contributes to shaping the future of accounting education and sustainability behavior among students in support of global environmental and social sustainability goals.